High-dose, intermediate-temperature neutron irradiation effects on silicon carbide composites with varied fiber/matrix interfaces. Issue 8 (July 2019) - Nozawa, Takashi; Koyanagi, Takaaki; Katoh, Yutai; Tanigawa, Hiroyasu
Abstract: SiC/SiC composites are promising structural candidate materials for various nuclear applications over the wide temperature range of 300–1000 °C. Accordingly, irradiation tolerance over this wide temperature range needs to be understood to ensure the performance of these composites. In this study, neutron irradiation effects on dimensional stability and mechanical properties to high doses (11–44 dpa) at intermediate irradiation temperatures (˜600 °C) were evaluated for Hi-Nicalon Type-S or Tyranno-SA3 fiber–reinforced SiC matrix composites produced by chemical vapor infiltration. The influence of various fiber/matrix interfaces, such as a 50–120 nm thick pyrolytic carbon (PyC) monolayer interphase and 70–130 nm thick PyC with a subsequent PyC (˜20 nm)/SiC (˜100 nm) multilayer, was evaluated and compared with the previous results for a thin-layer PyC (˜20 nm)/SiC (˜100 nm) multilayer interphase. Four-point flexural tests were conducted to evaluate post-irradiation strength, and SEM and TEM were used to investigate microstructure. Regardless of the fiber type, monolayer composites showed considerable reduction of flexural properties after irradiation to 11–12 dpa at 450–500 °C; and neither type showed the deterioration identified at the same dose level at higher temperatures (>750 °C) in a previous study. After further irradiation to 44 dpa at 590–640 °C, the degradation was enhanced compared with conventional multilayer composites with a PyC thickness of ˜20 nm. Multilayer composites have shown comparatively good strength retention for irradiation to ˜40 dpa, with moderate mechanical property degradation beginning at 70–100 dpa. Irradiation-induced debonding at the F/M interface was found to be the major cause of deterioration of various composites.